Concrete crossing slab as cover or closing for drainage at residential area / Saiful Hakim Fazal - Fazal, Saiful Hakim (Universiti Teknologi MARA, Perak, 2019)
Concrete crossing slab is one of the important elements of infrastructure work in building construction. It is used to facilitate the movement of the public surrounding. However, there are also a handful of projects that do not apply it and consider it a trivial thing. This report will discuss about the concrete crossing slab at the sidewalk of the residential area project. This report was conducted for concrete crossing slab at Batu Rakit, Kuala Nerus, Terengganu. The objective of this report is to find out the method construction used for this concrete crossing slab. It will focus on the proper procedure of construction that have been applied at the site. Next, to study the benefit of the concrete crossing slab and the suitable use of this slab based on site situation. All the meaning, this research about concrete crossing slab have been identified and can be use in the future wisely.